PERAN FOOD & BEVERAGE SERVICE DALAM MEMBERIKAN PELAYANAN UNTUK MENINGKATKAN KEPUASAN PELANGGAN DI MCDONALD’S JATIPADANG - Aulia Ananda; Gagih Pradini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Service is an activity carried out to meet the needs and desires expected by customers. The service is provided directly by the food & beverage service because it deals directly with customers. Food & beverage service has an important role in increasing the satisfaction of customers who come to the restaurant to create a good impression of the service and also the image of the restaurant. The purpose of this study was to determine the role of food & beverage service in providing services to increase customer satisfaction at McDonald's restaurants. The research method used is qualitative research. Data collection techniques using interview techniques, observation, documentation, and literature study. The results of this study can be seen that food & beverage service has a very influential role on the services provided by customers. It is proven that customers feel that the services provided can increase customer satisfaction with the restaurant and give a good impression to the restaurant.